Epidemiological characteristics and real‐world treatment outcomes of hepatitis C among HIV/HCV co‐infected patients in Myanmar: A prospective cohort study. Issue 2 (17th February 2023) - Swe, Thein Min; Johnson, Derek. C.; Mar, Htay Thet; Thit, Phone; Homan, Tobias; Chu, Cherry May; Mon, Phyu Ei; Thwe, Thin Thin; Soe, Kyi Pyar; Ei, Win Le Shwe Sin; Tun, Nyan Lynn; Lwin, Kyaw Zay; et al.
Abstract: Background and Aims: In Myanmar, public sector treatment programs for hepatitis C virus (HCV) infection were nonexistent until June 2017. WHO highlights the importance of simplification of HCV service delivery through task‐shifting among health workers and decentralization to the primary health care level. Between November 2016 and November 2017, a study was conducted to describe the epidemiological data and real‐world outcomes of treating HIV/HCV coinfected patients with generic direct acting antiviral (DAA) based regimens in the three HIV clinics run by nonspecialist medical doctors in Myanmar. Methods: HCV co‐infection among people living with HIV (PLHIV) from two clinics in Yangon city and one clinic in Dawei city was screened by rapid diagnostic tests and confirmed by testing for viral RNA. Nonspecialist medical doctors prescribed sofosbuvir and daclatasvir based regimens (with or without ribavirin) for 12 or 24 weeks based on the HCV genotype and liver fibrosis status. Sustained virologic response at 12 weeks after treatment (SVR12) was assessed to determine cure. Results: About 6.5% (1417/21, 777) of PLHIV were co‐infected with HCV. Of 864 patients enrolled in the study, 50.8% reported history of substance use, 27% history of invasive medical procedures and 25.6% history of incarceration. Data on treatment outcomes were collected from 267 patients of which 257 (96.3%) achieved SVR12, 7 (2.6%) failed treatment, 2 (0.7%) died and 1 (0.4%) became loss to follow‐up. Conclusion: The study results support the integration of hepatitis C diagnosis and treatment with DAA‐based regimens into existing HIV clinics run by nonspecialist medical doctors in a resource‐limited setting. Epidemiological data on HIV/HCV co‐infection call for comprehensive HCV care services among key populations like drug users and prisoners in Yangon and Dawei.